Economic and ecological benefit evaluation of geothermal resource tax policy in China - Yang, Yang; Jianmin, Zhang; Yaya, Hou; Xiaoxuan, Kao (Frontiers in Environmental Science, 2022)
Geothermal energy is a renewable energy source, and geothermal heating is a livelihood project, so a resource tax can protect resources and regulate prices. Reasonable geothermal energy resource tax collection standards are conducive to high-quality industrial development. This paper takes 15 provinces and cities that clearly levy geothermal resource taxes in China as the research object, constructs an SD (System Dynamics) model of geothermal resource tax, and studies the impact of geothermal resource tax on the income of geothermal enterprises and CO2 emission reduction. Then, the forecast simulates the economic and environmental benefits brought about by the use of geothermal resources from 2021 to 2035. The research results show that using geothermal resources for heating can significantly reduce CO2 emissions, and the higher the proportion of geothermal use is, the greater the CO2 emission reduction before 2035. The fifteen provinces and cities that clearly levy geothermal resource taxes will find it difficult to achieve corporate profits at the current residential heating utilization price and geothermal energy resource tax rate; that is, to achieve a balance of income and expenditures for geothermal enterprises without financial subsidies, the price of geothermal heating will be significantly higher than the heating price of traditional central heating and the price of electric self-heating.